Determinants Of EMR System Success: Integrating System Interoperability, Organizational Control Within The Hot-Fit Model - Sutiawan Sutiawan; Hosizah Markam; Rina Mutiara (International Journal of Economics, Management and Accounting, 2026)
Background, the implementation of an Electronic Medical Record (EMR) has become a crucial component in efforts to improve the quality of healthcare services in hospitals. The success of its implementation is not solely determined by technological factors but is also influenced by organizational readiness, the system’s ability to interoperate, and user support. Objective, this study aims to analyze the role of system interoperability and organizational control within the HOT-Fit Model framework to measure the level of success of EMR implementation at Mekar Sari Hospital. Methods, this study employed a quantitative research design with a cross sectional approach. Data analysis, the relationships among variables were examined using Structural Equation Modeling Partial Least Squares (SEM-PLS). Population and sample, the population consisted of all employees of Mekar Sari Hospital working across various service units, with a total sampling technique involving 120 respondents. Results, the findings indicate that technological factors, including system quality, information quality, and service quality, have a significant effect on system use and user satisfaction. Interoperability enhances information accuracy through more precise and consistent cross unit data integration. Organizational factors, particularly the organizational environment and organizational control, have a significant influence on structure, thereby supporting more optimal utilization of the EMR information system. Conclusion, this study recommends interoperability should be enhanced through data integration, standardization, and user training. In addition, organizations need to improve coordination, update standard operating procedures, strengthen audits, and optimize net benefits through measurable performance evaluations.